Spatial optimization of nutrient reduction measures on agricultural land to improve water quality: A coupled modeling approach - Brouwer, Roy; Pinto, Rute; Garcia‐Hernandez, Jorge; Li, Xingtong; Macrae, Merrin; Rajsic, Predrag; Yang, Wanhong; Liu, Yongbo; Anderson, Mark; Heyming, Louise (Canadian journal of agricultural economics, 2023)
The objective of this study is to identify the optimal spatial distribution of Best Management Practices (BMPs) to reduce total phosphorus (TP) runoff from agricultural land in the largest Canadian watershed draining into Lake Erie, the Great Lake most vulnerable to eutrophication. BMP measures include reduced fertilizer application, cover crops, buffer strips, and the restoration of wetlands. Environmental SWAT model results feed into a spatial optimization procedure using two separate objective functions to distinguish between public BMP program implementation costs (PIC) on the one hand and farmers’ private pollution abatement costs (PAC) on the other hand. The latter account for the opportunity costs of land retirement and changing land productivity. PAC are initially lower than PIC but exceed the latter after 30% of the annual TP baseline load is eliminated. This suggests that under optimal conditions existing grant and incentive payments cover the economic costs farmers face up to a maximum of 30% of the baseline load reduction. Imposing further reductions of up to 40% results in a cost to farmers of almost $52 million per year. This is 45% higher than the optimal solution based on PIC and therefore not deemed incentive‐compatible under the watershed's existing cost‐sharing scheme. Résumé L'objectif de cette étude est d'identifier la distribution spatiale optimale des meilleures pratiques de gestion (BMP) pour réduire le ruissellement de phosphore total (TP) des terres agricoles dans le plus grand bassin versant canadien qui se déverse dans le lac Érié, le Grand Lac le plus vulnérable à l'eutrophisation. Les mesures de BMP comprennent la réduction de l’épandage d'engrais, les cultures de couverture, les bandes tampons et la restauration des milieux humides. Les résultats environnemental du modèle SWAT alimentent une procédure d'optimisation spatiale utilisant deux fonctions objectives distinctes pour faire la distinction entre les coûts publics de mise en œuvre des programmes de BMP (PIC) d'une part et les coûts privés de réduction de la pollution (PAC) des agriculteurs d'autre part. Ces derniers tiennent compte des coûts d'opportunité de la mise hors service des terres et de l’évolution de la productivité des terres. Les PAC sont initialement inférieurs aux PIC, mais dépassent ce dernier après l’élimination de 30% de la charge de base annuelle de TP. Cela suggère que, dans des conditions optimales, les subventions et les primes d'incitation existantes couvrent les coûts économiques auxquels les agriculteurs sont confrontés jusqu’à un maximum de 30% de la réduction de la charge de base. L'imposition de réductions supplémentaires allant jusqu’à 40% entraîne un coût pour les agriculteurs de près de 52 millions de dollars par année. Il s'agit d'une augmentation de 45% par rapport à la solution optimale fondée sur le PIC et qui n'est donc pas jugée compatible avec les incitatifs dans le cadre du système actuel de partage des coûts du bassin versant.